Hybrid Evolutionary Computing Assisted Irregular-Shaped Patch Antenna Design for Wide Band Applications - Rohini Saxena; J. A. Ansari; Mukesh Kumar (International Journal of Electrical and Computer Engineering Systems, 2022)
A novel optimization concept for modeling irregular-shaped patch antenna with high bandwidth and efficient radiation attributes is proposed in this paper, along with the ability to accomplish the design at a reduced computational and cost burden. A revolutionary computing perception is established with Gravitational Search Algorithm (GSA) and Quantum Based Delta Particle Swarm Optimization (QPSO), now known as GSA-QPSO. The suggested model employed the GSA-QPSO algorithm strategically interfaced with a high-frequency structure simulator (HFSS) software through a Microsoft Visual Basic script to enhance irregular-shaped antenna design while maintaining wide bandwidth with suitable radiation efficiency over the target bandwidth region. The optimally designed microstrip patch antenna is fabricated on an FR-4 substrate with a surface area of 30×30×1.6 mm 3 . The evaluated outcome shows 96 % supreme radiation efficacy at 2.4 GHz whereas overall effectiveness is above 84% over the entire frequency range, with a nearly omnidirectional radiation pattern. In terms of impedance bandwidth, the suggested antenna offers 126.6 % over the operational frequency range from 2.34 GHz to 10.44 GHz. Fabrication and measurement results are also used to validate the simulated results. It exhibits the proficiency of the offered antenna design to be used for real-world wideband (WB) communication drives.